The role of academic libraries in research and teaching. (September 2019) - Klain Gabbay, Liat; Shoham, Snunith
The perceptions of faculty members from the faculties of social sciences and humanities regarding the role of the library in assisting with their research and teaching needs are compared with those of academic librarians. This research was designed as a comprehensive, mixed-methods study. First, interviews were conducted with faculty members and librarians; then, based on the findings, a questionnaire was constructed and distributed to faculty members and librarians in these departments. The main finding is that the contribution of library services to the various aspects of teaching and research is perceived as higher by the librarians than by the faculty members. Faculty members appear to expect more from the library in various aspects of research support; however, most faculty members believe that the library fulfils their teaching needs. Regarding research, faculty members believe most libraries support the technical aspects, but they do not support other aspects, such as locating the information or providing more comprehensive information relevant for the faculty members' research. Therefore it is important to compare and resolve the differences between faculty and librarians' perceptions. The findings of this study indicate that the perception in libraries needs to change, and some of these changes should be made already in the preparatory stages of the profession.